High temporal variability in airborne bacterial diversity and abundance inside single‐family residences. (31st October 2016) - Emerson, J. B.; Keady, P. B.; Clements, N.; Morgan, E. E.; Awerbuch, J.; Miller, S. L.; Fierer, N.
Abstract: Our homes are microbial habitats, and although the amounts and types of bacteria in indoor air have been shown to vary substantially across residences, temporal variability within homes has rarely been characterized. Here, we sought to quantify the temporal variability in the amounts and types of airborne bacteria in homes, and what factors drive this variability. We collected filter samples of indoor and outdoor air in 15 homes over 1 year (approximately eight time points per home, two per season), and we used culture‐independent DNA sequencing approaches to characterize bacterial community composition. Significant differences in indoor air community composition were observed both between homes and within each home over time. Indoor and outdoor air community compositions were not significantly correlated, suggesting that indoor and outdoor air communities are decoupled. Indoor air communities from the same home were often just as different at adjacent time points as they were across larger temporal distances, and temporal variation correlated with changes in environmental conditions, including temperature and relative humidity. Although all homes had highly variable indoor air communities, homes with the most temporally variable communities had more stable, lower average microbial loads than homes with less variable communities.